Sectoral Linkages in Pangandaran Regency’s Regional Development - Hendriany, Reni; Pravitasari, Andrea Emma; Rustiadi, Ernan (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2024)
Pangandaran District is a newly formed region in West Java Province. Effective and competitive regional development requires support from the potential leading sectors in a region. Prioritization is needed because of limited resources that cannot facilitate the development of all sectors simultaneously. This analysis aims to identify leading sectors, sector interconnections, and multiplier effects on the economy of Pangandaran Regency. The results are that there are 5 (five) sectors that are comparatively and competitively superior, namely: (1) Accommodation, Food and Drink Providers, (2) Agriculture, Forestry and Fisheries (3) Transportation and Warehousing, (4) Wholesale and retail trade , Repair and (5) Real Estate. The largest backward linkages are achieved by the "other services" sector. This sector becomes a lever for the development of its own sector. Meanwhile, the largest forward linkages are agriculture, forestry, and fisheries. The output from the agricultural sector is widely used as an input by other sectors. Agriculture, forestry and fisheries sectors are key sectors. This is because agriculture, forestry, and fisheries have the largest intersectoral linkages and dispersal index. The “Other services” sector is the largest output multiplier. The sector with the largest GRDP multiplier is agriculture, forestry and fisheries. Proper allocation of resources can be done by prioritizing the leading sectors to improve the regional development of the Pangandaran District.